LDOC1 is differentially expressed in thyroid cancer and display tumor‐suppressive function in papillary thyroid carcinoma. (17th January 2020) - Zhao, Shuiying; Zhao, Yanyan; Wang, Qingzhu; Li, Zhizhen; Ma, Xiaojun; Wu, Lina; Li, Wen; Du, Mengmeng; Ji, Hongfei; Qin, Guijun
Abstract: The leucine zipper downregulated in cancer 1 (LDOC1) has been proposed as a regulator of transcription and cell signaling. We have previously demonstrated that LDOC1 is differentially expressed in papillary thyroid carcinoma (PTC), this study was designed to characterize LDOC1 expression in thyroid follicle originated cancer tissues and to specifically evaluate its function in thyroid carcinogenesis. LDOC1 expression was performed in human normal thyroid and thyroid cancer. LDOC1 function was characterized, in two PTC cell lines (TPC1 and BCPAP), through the analysis of in vitro cell proliferation, apoptosis, migration, and invasion along with in vivo tumor xenograft growth. Transduced BCPAP cells were stimulated with tumor necrosis factor α, and the levels of nuclear P65, Bax, Bcl‐2, c‐Myc, and XIAP were assessed. A luciferase reporter assay was used to measure nuclear factor‐κB (NF‐κB) activity, and the functional connection between LDOC1 effect and NF‐κB activity was determined using a specific NF‐κB inhibitor. Our results revealed that LDOC1 was translocated from the nucleus to the cytoplasm in human thyroid cancer, and was significantly downregulated in PTC compared with normal thyroid. LDOC1 overexpression in TPC1 resulted in a significant suppression of the malignant phenotype, whereas LDOC1 ablation in BCPAP promoted this phenotype. Additional studies demonstrated that LDOC1 ablation facilitated nuclear P65 expression and NF‐κB activity. NF‐κB inhibition reversed the effects of LDOC1 ablation on proliferation, apoptosis, migration, and invasion. Our findings confirmed that LDOC1 is a novel therapeutic target in PTC and provides new insight into the role of LDOC1 in PTC progression, through NF‐κΒ signaling suppression.